(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article focuses on the problem of business names motivation in the context of discussion on semantic statues of proper nouns. The author argues for existence of four main motivation schemes of proper names – descriptive, metonymical, metaphorical and symbolical. Moreover, the connection between motivation type and proper name function is established.